The Vulnerable Financial Issue: Capital Flight in Indonesia - Basorudin, Muhammad; Kusmaryo, R. Dwi Harwin; Rachmad, Sri Hartini; Amannullah, Gantjang (The European Journal of Applied Economics, 2021)
Indonesia is a developing country with a high demand for capital from both domestic and international sources. However, international capital flow is the most needed. Capital flight is an adverse financial issue for non-western countries, especially Indonesia. This study aims to summarize the capital flight from Indonesia and analyse the effect of macroeconomic and non-macroeconomic determinants through capital flight. The macroeconomic determinants include budget deficit, economic growth, inflation rate, and exchange rate. The non-macroeconomic determinants are trade openness, interest rate differences, and dummy rating. The data are derived from Indonesian Central Bank, BPS-Statistics Indonesia, OECD, and Moody’s Investor Service. The coverage of this study is Indonesia in the period 2010 to 2018 quarterly. The period fits the latest Balance of Payment Manuals of the sixth edition (BPM 6) procedure. The measurements of capital flight in this study are the residual approach, the trade misinvoicing method, and the combined method. The result of this study shows that, compared to others, non-macroeconomics are the most influential determinants of capital flight from Indonesia.
Keywords: Capital Flight; Combined Method; Indonesia